2018
DOI: 10.1016/j.anaerobe.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Presence of multiple Clostridium difficile strains at primary infection is associated with development of recurrent disease

Abstract: Recurrence of Clostridium difficile infection (CDI) places a major burden on the healthcare system. Previous studies have suggested that specific C. difficile strains, or ribotypes, are associated with severe disease and/or recurrence. However, in some patients a new strain is detected in subsequent infections, complicating longitudinal studies focused on strain differences that may contribute to disease outcome. We examined ribotype composition over time in patients who did or did not develop recurrence to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
15
3
Order By: Relevance
“…Reports of patients infected with multiple strains of C. difficile suggest that despite our results, infection with multiple strains can occur (21, 22). When we infected mice with different ratios of spores from each of the two strains simultaneously, we found that both strains were capable of colonizing despite starting with over a 1000x less str.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…Reports of patients infected with multiple strains of C. difficile suggest that despite our results, infection with multiple strains can occur (21, 22). When we infected mice with different ratios of spores from each of the two strains simultaneously, we found that both strains were capable of colonizing despite starting with over a 1000x less str.…”
Section: Resultscontrasting
confidence: 83%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted February 27, 2021. ; https://doi.org/10.1101/2021.02.26.433146 doi: bioRxiv preprint Reports of patients infected with multiple strains of C. difficile suggest that despite our results, infection with multiple strains can occur (21,22). When we infected mice with different ratios of spores from each of the two strains simultaneously, we found that both strains were capable of colonizing despite starting with over a 1000x less str.…”
Section: Protection Afforded By Low Virulence C Difficile Strain Devcontrasting
confidence: 52%
“…In a previous report, the same C. difficile ribotypes isolated at baseline were also isolated over a long period of time (14 to 56 days) in recurrent CDI cases (31). Therefore, the differences in the timing of sampling for analysis of C.…”
Section: Discussionmentioning
confidence: 67%
“…It is possible that we would have detected more frequent within-host genetic diversity if we had sampled more than 8 colonies per culture. In a previous study in adults (15), 36 colonies per culture were isolated from adults with CDI, and half of the cultures had more than 1 (median of 2) unique ribotype; the presence of multiple ribotypes at the time of initial CDI was associated with subsequent CDI recurrence.…”
Section: Discussionmentioning
confidence: 91%